Attitudes Towards Nasimi in Modern Literature - Amonova, Zilola (FILOLOGIYA UFQLARI JURNALI, 2024)
The article deals with the impact o f the work o f the talented Azeri poet Imodiddin Nasimi on Uzbek literature. The poems o f the great poet have been a source o f inspiration fo r our artists since time immemorial. This aspect can also be seen in modern Uzbek literature. Abdulhamid Chulpon. who worked in the early years o f the twentieth century, writes poems in harmony with Nasimi’s ideas. The article analyzes such poems by Cholpon. In addition, the poems o f Usmon Koch к or. S. Say id. poetess Nodira Afokova. Amir Khudoiberdi. Nasimi’s name and passion are discussed.